Multidrug-resistant tuberculosis - Dheda, Keertan; Mirzayev, Fuad; Cirillo, Daniela Maria; Udwadia, Zarir; Dooley, Kelly E.; Chang, Kwok-Chiu; Omar, Shaheed Vally; Reuter, Anja; Perumal, Tahlia; Horsburgh, C. Robert; Murray, Megan; Lange, Christoph (Nature reviews. Disease primers, 2024)
Tuberculosis (TB) remains the foremost cause of death by an infectious disease globally. Multidrug-resistant or rifampicin-resistant TB (MDR/RR-TB; resistance to rifampicin and isoniazid, or rifampicin alone) is a burgeoning public health challenge in several parts of the world, and especially Eastern Europe, Russia, Asia and sub-Saharan Africa. Pre-extensively drug-resistant TB (pre-XDR-TB) refers to MDR/RR-TB that is also resistant to a fluoroquinolone, and extensively drug-resistant TB (XDR-TB) isolates are additionally resistant to other key drugs such as bedaquiline and/or linezolid. Collectively, these subgroups are referred to as drug-resistant TB (DR-TB). All forms of DR-TB can be as transmissible as rifampicin-susceptible TB; however, it is more difficult to diagnose, is associated with higher mortality and morbidity, and higher rates of post-TB lung damage. The various forms of DR-TB often consume >50% of national TB budgets despite comprising <5–10% of the total TB case-load. The past decade has seen a dramatic change in the DR-TB treatment landscape with the introduction of new diagnostics and therapeutic agents. However, there is limited guidance on understanding and managing various aspects of this complex entity, including the pathogenesis, transmission, diagnosis, management and prevention of MDR-TB and XDR-TB, especially at the primary care physician level. Multidrug-resistant tuberculosis (MDR-TB) is caused by Mycobacterium tuberculosis that is resistant to several first-line drugs. MDR-TB is an increasing public health challenge. In this Primer, Dheda et al. summarize the epidemiology and mechanisms, and discuss diagnosis, management and quality of life of patients with MDR-TB.